Die Frauenbewegung in Deutschland - Freimuth, W. (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1881)
One of a series of tracts on contemporary social and literary concerns. Freimuth supports the women's movement, but urges caution and restraint.